IP BPM position error at CLIC due to secondary emission from beam-beam BACKGROUNDS - Hartin, A; Clarke, C; Swinson, C; Burrows, P; Christian, G; Constance, B; Apsimon, R; Khah, H; Perry, C; Kalinin, A (European Physical Society Accelerator Group (EPS-AG), 2008)
Beam-beam background impacts on the IP BPM are studied for the CLIC machine. The large number of coherent pairs (1.8 × 108 charges per BPM strip per bunch crossing) for the CLIC-G default parameter set, potentially leads to a large secondary emission in the BPM strips. Detailed GuineaPig++ and Geant studies reveal, however, that the coherent pairs travel down the extraction line without significant secondary showering. Geant studies of the CLIC incoherent pairs show a flux of secondary emission two orders of magnitude less than that expected for the ILC 1 TeV high luminosity scheme. Since previous studies showed that FONT IP BPM signal distortion for the ILC was of no concern, then it can also be neglected at CLIC.